1989
DOI: 10.1164/ajrccm/139.3.791
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Rhinitis: II. Assessment of the Sources of Protein in Histamine-induced Nasal Secretions

Abstract: Nasal provocation tests were performed on nine atopic and 15 nonatopic subjects in order to assess the sources of protein in histamine-induced secretions and to examine the bilateral secretory response to unilaterally applied topical histamine (the nasonasal reflex). Nasal lavages were assayed for the following proteins: albumin, total protein, secretory IgA (sIgA), nonsecretory IgA (serum IgA), and total IgA. Histamine stimulation produced a profound ipsilateral protein secretion enriched in the serum protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 5 publications
5
90
0
4
Order By: Relevance
“…In addition, serous and mucous secretion into the nasal cavity reduce its patency. Both bradykinin and histamine induce this secretion (Baraniuk et al, 1990;Raphael et al, 1989) and differences in their potencies may reflect the inability of L-NAME to attenuate histamine-induced nasal blockage. The patency of the nasal cavity is also reduced by swelling of the nasal mucosa resulting from increased microvascular permeability and increased blood flow.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, serous and mucous secretion into the nasal cavity reduce its patency. Both bradykinin and histamine induce this secretion (Baraniuk et al, 1990;Raphael et al, 1989) and differences in their potencies may reflect the inability of L-NAME to attenuate histamine-induced nasal blockage. The patency of the nasal cavity is also reduced by swelling of the nasal mucosa resulting from increased microvascular permeability and increased blood flow.…”
Section: Resultsmentioning
confidence: 99%
“…Some investigations indicate that histamine caused sneezing and nasal rubbing by its binding to H 1 -receptors on sensory nerve endings. [18][19][20][21] As a matter of course, there are some findings that histamine H 1 -receptor antagonists inhibited the symptoms of sneezing and nasal rubbing of allergic rhinitis model in mice and rats. 22,23) Moreover, other investigators have shown that the suppression of antigen-specific IgE production inhibited the nasal symptoms of an allergic rhinitis model.…”
Section: Discussionmentioning
confidence: 99%
“…The sources of human nasal secretions have been previously analyzed by measuring the secretion of albumin (Alb),I secretory IgA (sIgA), nonsecretory IgA, and IgG into induced nasal secretions (1,2).2 It was demonstrated that sIgA is a protein produced locally in the nasal mucosa, processed exclusively by the submucosal glands (1). The secretion of sIgA into nasal secretions is regulated by processes that govern glandular secretion (e.g., the cholinergic nervous system), and therefore sIgA can be used as a marker of glandular secretion.…”
Section: Introductionmentioning
confidence: 99%